Implications of Conventional and Organic Coffee Farming Systems on Soil Chemical Properties - Husna Husna; Tandaditya Ariefandra Airlangga; AH Maftuh Hafidh Zuhdi; Hafiz Luthfi (Universitas Muhammadiyah Kotabumi, 2026)
ABSTRACT The coffee cultivation system has important implications for soil quality, particularly soil chemical properties that play a role in supporting plant growth and productivity. This study aimed to analyze the implications of conventional and organic coffee cultivation systems on soil chemical properties in West Lampung Regency. The research was conducted from March to September 2025 using a survey method with a comparative approach. Soil samples were collected at a depth of 0–20 cm from coffee fields managed under conventional and organic cultivation systems, with three replications for each system. The parameters analyzed included soil pH, organic carbon (C-organic), total nitrogen (N-total), available phosphorus (P-available), available potassium (K-available), and cation exchange capacity (CEC). Data were analyzed using analysis of variance (ANOVA), followed by the Least Significant Difference (LSD) test at the 5% level when significant differences were observed. The results showed that the coffee cultivation system had a highly significant effect on soil pH, organic carbon content, and available phosphorus. The organic cultivation system exhibited higher soil pH (6.30), organic carbon (2.35%), and available phosphorus (19.00 mg kg⁻¹) compared to the conventional system. Meanwhile, total nitrogen, available potassium, and CEC did not show significant differences between cultivation systems. These findings indicate that organic coffee cultivation is more effective in improving soil chemical properties related to soil reaction and nutrient availability, thereby potentially supporting the sustainability of coffee agroecosystems.